2009
DOI: 10.1002/hed.20988
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection for the management of the N0 neck in early cancer of the oral tongue: Need for a randomized controlled trial

Abstract: END did not impact disease-free or OS. Current literature still remains divided on this issue emphasizing the need for a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 33 publications
5
88
0
Order By: Relevance
“…Since the presence of occult metastases is an additional risk factor, which might reduce patients overall and disease-free survival time, several authors argue, that all patients with OSCC and clinically N0 neck should receive elective neck dissection (Capote et al, 2007;Cheng and Schmidt, 2008). The results of other studies, however, suggest that a "watchful-waiting" strategy with regular examination intervals and salvage treatment in case of loco-regional recurrence might be sufficient to achieve similar overall and disease-free survival rates in OSCC patients with early tumours and a clinically N0 neck (D'Cruz et al, 2009). Our retrospective analysis, however, demonstrated that the presence of occult metastases is associated with a reduction of the overall and disease-free survival time of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…Since the presence of occult metastases is an additional risk factor, which might reduce patients overall and disease-free survival time, several authors argue, that all patients with OSCC and clinically N0 neck should receive elective neck dissection (Capote et al, 2007;Cheng and Schmidt, 2008). The results of other studies, however, suggest that a "watchful-waiting" strategy with regular examination intervals and salvage treatment in case of loco-regional recurrence might be sufficient to achieve similar overall and disease-free survival rates in OSCC patients with early tumours and a clinically N0 neck (D'Cruz et al, 2009). Our retrospective analysis, however, demonstrated that the presence of occult metastases is associated with a reduction of the overall and disease-free survival time of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of nodal metastasis is higher for early cancer of the tongue when compared with other sites of the oral cavity. AK D'cruz et al found the incidence of nodal metastasis to be 37.5% in T1 lesions and 62.5% in T2 lesions of the oral tongue [9]. Andersen et al studied the results of neck failure following observation of N0 necks.…”
Section: Discussionmentioning
confidence: 99%
“…Many histo-pathologic features have been previously investigated as risk factors for occult cervical lymph node metastasis in early OTC but there is no consensus [9,10,18] and there is still controversy regarding the management of clinical N0 neck [19]. The PVI and PLI are identified as the factors of RR but no statistical difference in DFS or OS between elective treatment and observation groups in the present study.…”
Section: Discussionmentioning
confidence: 49%